EXPRESSING FORMULAS OF DIRECT REFUSALS OF OFFERS BY VIETNAMESE - Vương Thị Hải Yến (Tạp chí Khoa học Đại học Đà Lạt)
Refusals, like other speech acts, occur in all languages. They are used to express the declination of requests, offers, invitations, and suggestions, etc., in conversations. Refusal is commonly expressed by the Vietnamese through two direct or indirect means of expression, including grammatical structures and semantic formulas. This study focuses on formulas expressing indirect refusals of offers by Vietnamese.